2006
DOI: 10.4049/jimmunol.177.12.8476
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Distinct Membrane Nanotubes between Human Macrophages Support Long-Distance Vesicular Traffic or Surfing of Bacteria

Abstract: We report that two classes of membrane nanotubes between human monocyte-derived macrophages can be distinguished by their cytoskeletal structure and their functional properties. Thin membrane nanotubes contained only F-actin, whereas thicker nanotubes, i.e., those > approximately 0.7 microm in diameter, contained both F-actin and microtubules. Bacteria could be trapped and surf along thin, but not thick, membrane nanotubes toward connected macrophage cell bodies. Once at the cell body, bacteria could then be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
520
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(565 citation statements)
references
References 39 publications
26
520
1
9
Order By: Relevance
“…These nanotubes were shown to facilitate the transfer of lipid organelles between cells through actindependent mechanism. Nanotube structures were also reported to connect a wide range of immune cells, such as T cells, B cells, NK cells, and monocytes (24,75). In the event of disassembly of immunological synapse, formation of membrane nanotubes was observed between B cells and NK cells (76).…”
Section: Membrane Nanotube Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanotubes were shown to facilitate the transfer of lipid organelles between cells through actindependent mechanism. Nanotube structures were also reported to connect a wide range of immune cells, such as T cells, B cells, NK cells, and monocytes (24,75). In the event of disassembly of immunological synapse, formation of membrane nanotubes was observed between B cells and NK cells (76).…”
Section: Membrane Nanotube Formationmentioning
confidence: 99%
“…Thicker nanotubes are made up of both F-actin and microtubules, whereas thinner ones contain only F-actin. It was shown that nanotubes containing microtubules transport vesicles over long distances, whereas, using a constitutive flow of nanotube surface, bacteria "surf" along nanotubes that lack microtubules (75). Surface transport along thin nanotubes was found to be dependent on ATP but independent of microtubules.…”
Section: Membrane Nanotube Formationmentioning
confidence: 99%
“…"The crucial thing is deciding what you're going to dig into and investigate. " His team went on to describe different sorts of nanotube, some holding vesicles and mitochondria inside, and others with bacteria 'surfing' the casing 5 .…”
Section: Long Pipelinementioning
confidence: 99%
“…NTs may provide routes for extensive exchange of information (specific signals) or biomatter between cells. Trafficking of vesicles [10], calcium ions [11], viral proteins [12], bacteria [10], cytoplasmic molecules, organelles, plasma membrane (PM) components or mRNA [9,11] were observed either inside NTs or on their outer surfaces, suggesting involvement of various motor proteins (myosins, dyneins, or kinesins). Such processes can influence cell development, differentiation, effector functions or cell death in both the innate and adaptive immune systems [13].…”
Section: Membrane Nanotubes (mentioning
confidence: 99%